Tracking Neural Deterioration in proNGF-Overexpressing Mice: Hippocampal Serotonergic Dysfunction and Synaptic Loss Drive Neurodegeneration (Translation: The University of Toledo Journal of Medical Sciences, 2025)
ProNGF, the precursor protein of mature nerve growth factor (NGF), plays a complex role in neural signaling and has been implicated in neurodegeneration through its apoptotic signaling with the p75NTR receptor. For example, in Alzheimer's disease increased levels of proNGF are associated with cholinergic neuron loss and excitatory/inhibitory imbalance. This study deploys cutting edge a bioinformatic analyses of RNAseq data from TgproNGF#3 mice models that express furin-resistant proNGF. The TgproNGF#3 mouse mimics the pathological accumulation of the precursor NGF protein observed in these diseased brains. Our analysis revealed that proNGF accumulation in the hippocampus and entorhinal regions leads to early downregulation of genes critical for neuronal communication, such as pion and KCNAB2, and later to the upregulation of stress-related and signaling genes, including Neurod1, Neurod2, and Gnai1. These shifts in gene regulation suggest that while the brain attempts to counteract the excess in proNGF, its delay and inefficacy may contribute to early-stage Alzheimer's disease processes.
Keywords: Alzheimer's Disease; animal model; pathways; Transcriptomic profiles; DEG's; nerve growth factor; hippocampus; Gnai1; KCNAB2; neurodegeneration